2013
DOI: 10.1038/pr.2013.105
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood television viewing and kindergarten entry readiness

Abstract: Background:Using a large population-based sample, this study aims to verify whether televiewing at 29 mo, a common early childhood pastime, is prospectively associated with school readiness at 65 mo. Methods: Participants are a prospective longitudinal cohort of 991 girls and 1,006 boys from the Quebec Longitudinal Study of Child Development with parent-reported data on weekly hours of televiewing at 29 mo of age. We conducted a series of ordinary least-squares regressions in which children's scores on direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 41 publications
2
92
2
1
Order By: Relevance
“…The negative impact of TV viewing on physical development has been shown in children under 6 years of age. A prospective, longitudinal study that evaluated the relationship between TV watching at 29 months old and physical strength at 65 months of age in 1997 Canadian children reported that gross motor skills were reduced by high screen time …”
Section: Physiological Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative impact of TV viewing on physical development has been shown in children under 6 years of age. A prospective, longitudinal study that evaluated the relationship between TV watching at 29 months old and physical strength at 65 months of age in 1997 Canadian children reported that gross motor skills were reduced by high screen time …”
Section: Physiological Developmentmentioning
confidence: 99%
“…Similarly, a longitudinal study reported that children with higher TV viewing at 29 months of age exhibited less school readiness at 65 months of age. This manifested as decreased vocabulary and number knowledge scores as well as lower classroom engagement …”
Section: Psychological Developmentmentioning
confidence: 99%
“…Parental mental and physical health problems are associated with cognitive and other delays in young children (Breaux, Harvey, & Lugo-Candelas, 2013). Toddlers and preschool-aged children who frequently watch television are more likely to enter school with lower academic functioning, particularly in reading (Pagani, Fitzpatrick, & Barnett, 2013). This is possibly due to television viewing displacing storybook reading (Koolstra & Van der Voort, 1996) and limiting growth in children’s cognitive and attentional capacities (Christakis, Zimmerman, DiGiuseppe, & McCarty, 2004).…”
Section: Potential Confounds Of the Theorized Relation Between Oral Vmentioning
confidence: 99%
“…By contrast, studies have shown that time that children spend reading traditional books has decreased to between 19 and 28 minutes per day . The documented negative effects of screen time, which includes the use of screen‐based media such as smartphones, tablets, desktop or laptop computers and television, include language delay , obesity , decreased readiness for kindergarten and other academic problems and exacerbation of attention deficit hyperactive disorder . It has been proposed that major drivers of these effects are decreased engagement with grown‐up caregivers and the displacement of active endeavours such as reading, homework and creative play .…”
Section: Introductionmentioning
confidence: 99%